2008
DOI: 10.1016/j.etap.2007.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxidative stress in the promoting activities of PCBs

Abstract: PCBs are organic pollutants that persist and bioaccumulate in the environment. These chemicals induce and promote liver tumors in rodents. Previous studies have shown that they increase oxidative stress in the liver, including lipid peroxidation, oxidative DNA damage, and NF-κB activation. The objective of these studies was to determine if the promoting activities of PCBs could be inhibited by dietary antioxidants (vitamin E, selenium, or phytochemicals) or by knocking out the p50 subunit of NF-κB. In the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 23 publications
3
24
0
Order By: Relevance
“…In this respect, in a recent study, Alegría-Torres et al (Frigo et al, 2004;Kim et al, 2004). Similar findings were found for PCBs (Bezdecny et al, 2007;Glauert et al, 2008;Myhre et al, 2009;Wang et al, 2008). In line with the mechanism proposed by Champion et al (2013), our data showed that the over-expression of AhR was dependent on the TNF induced by DDE and PCB 153.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In this respect, in a recent study, Alegría-Torres et al (Frigo et al, 2004;Kim et al, 2004). Similar findings were found for PCBs (Bezdecny et al, 2007;Glauert et al, 2008;Myhre et al, 2009;Wang et al, 2008). In line with the mechanism proposed by Champion et al (2013), our data showed that the over-expression of AhR was dependent on the TNF induced by DDE and PCB 153.…”
Section: Discussionsupporting
confidence: 79%
“…Those findings indicated that AhR expression in FLSs was stimulated in the presence of TNF, similar to our results here. Taking into account that data and our own, we hypothesize that TNF induced by DDE and PCB 153 (Alegría-Torres et al 2009; Cárdenas-González et al, 2013), likely via an NF-B pathway (Bezdecny et al, 2007;Frigo et al, 2004;Glauert et al, 2008;Kim et al, 2004;Myhre et al, 2009;Wang et al, 2008), was able to induce AhR mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we proposed an oxidative stress-like mechanism inductor of hepatic and renal damage after acute oral administration of BDE-99 in adult male rats. This hypothesis was based on the results of recent studies showing that exposure to certain environmental toxicants such as PCBs, caused disorders through oxidative damage in rodents (Schlezinger et al, 2006;Glauert et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, curcumin has shown significant impact in reducing oxidative stress induced by environmental pollutants such as metal nanoparticles, polychlorinated biphenyls (PCBs), etc. [36, 37]. Furthermore, our recent efforts found that curcumin, and potentially other polyphenols (e.g., quercetin), have shown binding affinities to environmental contaminants (e.g., PCBs).…”
Section: Introductionmentioning
confidence: 99%